ENT 600: Six side : Trextractor / Muhamad Fikri Mohd Yunos … [et al.] - Mohd Yunos, Muhamad Fikri; Indera Fauzi, Intan Noormaizura; Selamat, Siti Ayisah; Ismail, Suraya Hanna (2016)
• The team is developing a Multi-purpose Plantation Extractor. We have contributed an idea to produce this machine called TREXTRACTOR. • This TREXTRACTOR is designed with combination of three different types of extractor of different plantation types into one innovation. • This Multi-purpose Plantation Extractor can harvest oil palm bunch, latex from rubber tree and coconut for food production and business purposes. • Nowadays, plantation industry in Malaysia is still using manual harvesting equipment which is time consuming. • This machine is specially invented for huge industry also small industry for high yield of product in short period of time. • This multipurpose extractor is able to detect the types of plant to be harvested automatically. • This machine is safe to use and can avoid from any injuries as the blade is located within the machine. • Our machine is also sell at the market with affordable price. 1.1.2 Background study • The current way of plucking of palm, latex and coconut from tree: Rubber tapping and Drainage Knife > V -shaped front edge which used to apply on the tree trunks through which rubber fluid slowly flows out. > Manually tapping by human. Palm oil and coconut tree > Manually harvesting by using chisel and sickle as cutting tool which required more energy and need an accurate angle to cut.